Efektivitas Konten Short-Video dalam Penyampaian Pesan Dakwah di Era Generasi Z - Chanelza Virgantara; Dwiana Putri Purwani; Mila Septriasa; Suci Supiah; Syarip Hidayat (IAINU Kebumen, 2026)
Digital technology development has transformed da'wah delivery from conventional methods to social media platforms, aligning with Generation Z’s preference for visual, concise, and interactive information. This study aims to measure the effectiveness of short-video content in conveying da'wah messages among PGSD students, representing Generation Z and future educators. Using a quantitative approach with descriptive survey method, data were collected through a Likert-scale questionnaire from 27 respondents and analyzed using descriptive statistics to determine mean scores and percentages. The results show a global average score of 4.12, categorized as very effective, with accessibility being the strongest aspect, while message retention and sharing intention scored lower due to duration limitations and social factors. Statistically, the hypothesis was accepted, proving that short-video content effectively conveys da'wah messages through aesthetic, clear, and contextual presentation. Despite limitations regarding material depth, this medium is considered relevant and capable of influencing positive attitudes and behaviors, making it an adaptive and sustainable digital da'wah strategy.